Studi Variasi Ubi Jalar (Ipomoea Batatas L) Berdasarkan Karakter Morfologi di Kabupaten Ngawi - Karlina Purbasari; Angga Rahabistara Sumadji (Florea : Jurnal Biologi dan Pembelajarannya, 2018)
Sweet potatoes were potential plants in food diversification for rice substitution. The plants could be found in some areas in Indonesia, such as in Ngawi Regency. The research aimed to find out the variation and morphological distinction in sweet potatoes in Ngawi Regency. The samples were taken randomly in Kedunggalar, Jogorogo, and Bringin Subdistrict. The sweet potatoes were tested with ANAVA and DMRT, Kruskal-Wallis and U-Mann Whitney with significant degree was 5%. There were variation in morphological leaves, storage root, and stems from the eight samples taken. Statistical analysis showed there were vivid distinction in the shape of the leaves, the lobes type, the central lobes, the petiole pigmentation, the colour of stems, the immature leaves colour, the storage roots shape, the dominant skin colour, the dominant flesh colour, and distribution of secondary flesh colour of anthosianine pigment. The variation among sweet potatoes were affected by genetic/ variety distinction and environment factors.